Depolarization as a regulatory signal at voltage-gated calcium channels. - Triggle David J. (Acta Pharmacologica Sinica, 2016)
Changes in membrane potential are a regulatory signal for voltage-gated ion channels including the family of Ca2+ channels. This regulatory role includes the voltage-dependent opening, closing, and inactivation of ion channels and the control of drug access and affinity for discrete channels states. Membrane potential is both a short- and long-term regulatory signal controlling the number and function of these voltage-gated channels. Depolarization of neuronal and neurosecretory cells produces down-regulation of L-type voltage-gated Ca2+ channels. These processes are described and their relevance to physiologic and pathologic processes of neuronal development and neuroprotection are indicated.